Jacobi-type block matrices corresponding to the two-dimensional moment problem: polynomials of the second kind and Weyl function - Dudkin, M. Ye.; Kozak, V. I. (Ukrains’kyi Matematychnyi Zhurnal, 2016)
We continue our investigations of Jacobi-type symmetric matrices corresponding to the two-dimensional real power moment problem. We introduce polynomials of second kind and the corresponding analog of the Weyl function.